IMPROVEMENT OF TEACHERS AND ADMINISTRATIVE ABILITIES IN OPERATING WEB-BASED APPLICATIONS (GOOGLE FORM) THROUGH IN-HOUSE TRAINING METHOD IN UNGGULAN 1 TANA TIDUNG INTEGRATED STATE HIGH SCHOOL - Eko Indayani (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
Teacher competence in operating computers is still low, the willingness of teachers to operate online applications is lacking, teachers' indifference to technology science, not having the courage to operate computers, and feelings of inferiority to computer knowledge have resulted in less than optimal teachers and educational staff in carrying out their main tasks and functions. Therefore, the researcher who is also the Principal of the School conducts School Action Research through the application of In House Training in Operating Web-Based Applications (Google Form) for Teachers and Education Personnel. This research is a school action research that aims to describe how to improve the ability of teachers and education personnel of SMA Negeri Terpadu 1 Tana Tidung in operating web-based applications through In House Training. This research was conducted from January 22, 2020 to January 25, 2020 at SMA Negeri Terpadu Unggulan 1 Tana Tidung on Jl. Perintis RT 01 Kec. Sesayap Kab. Tana Tidung. The data analysis technique used is qualitative data analysis techniques for the results of observations, training results, and interviews. From the results of the study, it is known that in the first cycle of 40 participants, the average score was in the good category. However, there were still several obstacles such as some participants who were still not fluent in operating the Google Form in making online questionnaires, cooperation between participants in the group was still lacking, and there were still some participants whose scores were still sufficient. In the second cycle, it was obtained that the participants' average score was in the very good category. This indicates an increase in yield in the previous cycle. This also occurs because of a better planning to overcome deficiencies in cycle II. The things that were obtained in the application in cycle II that made the results of the training of participants increase are (1) good preparation from before that was done by the speaker before teaching; (2) enthusiastic participants in participating in the training because most of the participants began to give opinions, were motivated in doing assignments, responded to other people's opinions, and collaborated with other participants; (3) Participants begin to cooperate with each other in solving mutual problems, this can be seen from the participants who understand the material starting to teach their group of friends who do not understand; (4) Participants are more enthusiastic about participating in the training, this is because there is an award at the end of the meeting. Based on the results of this study, it can be concluded that the ability of teachers and educational staff in operating web-based applications via google form has increased.